Nationalists Who Feared the Nation : Adriatic Multi-Nationalism in Habsburg Dalmatia, Trieste, and Venice. - Reill, Dominique (Stanford University Press, 2012)
We can often learn as much from political movements that failed as from those that achieved their goals. Nationalists Who Feared the Nation looks at one such frustrated movement: a group of community leaders and writers in Venice, Trieste, and Dalmatia during the 1830s, 40s, and 50s who proposed the creation of a multinational zone surrounding the Adriatic Sea. At the time, the lands of the Adriatic formed a maritime community whose people spoke different languages and practiced different faiths but identified themselves as belonging to a single region of the Hapsburg Empire. While these acti.